Common European Origin of Hepatitis E Virus in Human Population From Eastern Romania - Porea, Daniela; Anita, Adriana; Vata, Andrei; Teodor, Danut; Crivei, Luciana; Raileanu, Cristian; Gotu, Vasilica; Ratoi, Ioana; Cozma, Andreea; Anita, Dragos; Oslobanu, Luanda; Pavio, Nicole; et al. (Frontiers in Public Health, 2020)
The purpose of this research was to improve the epidemiological data on HEV infection in the human population in Romania. The analysis targeted hospitalized subjects with acute hepatitis (n = 94) of unknown etiology from the Infectious Diseases Regional Hospital in Iasi. Moreover, patients without liver disease (n = 40) from a different county hospital located in Eastern Romania were included. The presence of HEV infection and first characterization of human HEV strains was determined using serological and molecular assays. The apparent HEV seroprevalence varied between 29.16% (95% CI, 16.31–42.03) and 32.5% (95% CI, 17.98–47.02) according to patient grouping. Molecular analysis enhanced the detection of two HEV isolates, that clustered in subtype HEV-3c, the most commonly identified subtype in Europe. Identification of acute hepatitis E cases, together with the first detection and molecular characterization of human HEV in Romania represent the originality attributes of the present study.